The Joint Contribution of Activation and Inhibition in Moderating Carryover Effects of Anger on Social Judgment - Fiori, Marina; Shuman, Vera (Frontiers in Psychology, 2017)
Carryover effects of emotions that lead to biases in social judgments are commonly observed. We suggest that such effects may be influenced by the ability to engage or disengage attention from emotional stimuli. We assessed the ability to activate and inhibit attention to anger stimuli, experimentally induced anger in a demanding task, and measured social judgement toward an ambiguous target. Results show that higher activation and higher inhibition of anger-related information predicted more biased evaluations of the ambiguous target when individuals were experiencing anger, but not in an emotionally neutral condition. Interestingly, the effect of activation and inhibition in the anger condition emerged only when such variables were entered simultaneously in the regression model, indicating that they had an additive effect in predicting carryover effects of anger on social judgement. Results are consistent with a cooperative suppression effect (Conger, 1974) of activation and inhibition and may be explained by either an increased accessibility of anger-related cues leading to more biased social judgments or by an instance in which being good at engaging in and disengaging attention from motional cues might have depleted participants’ resources making carryover effects of anger more likely to occur. Ultimately findings highlight that individual differences in attentional processes are important moderators for carryover effects of emotions.